But It is Still Progress, Progress, Progress - Kostlán , Antonín (Dějiny – teorie – kritika, 2009)
This article is devoted to the topic of ‘progress’ in the broader perspective of cultural history. The author presents a series of iconographic materials, from Early Modern depictions of hierarchic linear arrangements, through the apotheosis of technological-scientific progress and the historicizing heroization of the nineteenth century, all the way to caricatures of the present with their links to earlier models and using icons of biological evolution with its turning back to individualist regression.